Healthy animals, healthy people: Inextricably linked - Cates, Michael B. (My University, 2009)
Dogs and dolphins, monkeys and cats, horses and mules, rabbits, rodents, reptiles, and humans--multiple species, and all are part of the focused mission of the US Army Veterinary Corps. For over 91 years, officers in our Corps, along with support personnel, have been an integral part of the Army Medical Department, making critical global contributions toward the health of animals, as well as the health of Soldiers, Family members, and others. The US Army Veterinary Corps was formed in 1916 at a time when our country was just beginning to comprehend the relationship between animal and human health. We now know that those ties are tremendous. With extraordinary versatility and vigilance, our relatively small veterinary team of 3500 total personnel has continued its quest of the Army version of “One Medicine, One Health.”
Keywords: Veterinary medicine; Healthy animals; Healthy people; Zoonoses; Health linkages